Comparison of the Ability of Different Types of Birds to Derive Energy from Corn and Soybean Meal - Nahid Zahroojian; Hossein Moravej; Mojtaba Zaghari; Saied Aminzadeh (Poultry Science Journal)
This study evaluated the ability of different types of birds to derive energy from corn and soybean meal (SBM) using the reference diet substitution method. The corn and SBM were combined into a reference diet at 60 and 30%, respectively. Other ingredients, including dicalcium phosphate, limestone, salt, minerals, vitamins, and amino acids, held constant across the reference and test diets.  A total of 36 broiler breeder hens (Ross 308, 62 weeks old), 72 male broiler chickens (Ross 308, 35 days old) and 36 commercial layer hens (Hy-line W36, 40 weeks old) were used. The apparent metabolizable energy corrected for zero nitrogen retention (AMEn), apparent ileal digestible energy (AIDE) of corn and SBM and apparent ileal digestibility coefficient (AIDC) of nitrogen, crude fat and gross energy for whole diets were evaluated. The activities of intestinal digestive enzymes and intestinal morphology were measured and compared among the dietary treatments and birds. The AMEn of SBM for broiler breeder hens was significantly higher than that of broiler chickens and commercial layer hens (2525.50, 2215.10 and 2310.80 kcal/kg DM respectively; P < 0.05); in contrast, the corn AMEn for broiler breeder hens was lower than that of broiler chickens and laying hens (3126.67, 3382.11 and 3305.59 kcal/kg DM respectively; P < 0.05).  The AIDE values of corn and SBM were not significantly different between the subjected birds (P > 0.05). Furthermore, the difference between AMEn and AIDE for both corn and SBM was not significant in any experiment (P > 0.05). In conclusion, the findings of this study indicate that broiler breeder hens have a distinct capacity for deriving energy from corn and SBM compared to broiler chickens and layer hens. This highlights the impracticality of using a single set of energy values for these feedstuffs in poultry feed formulations.